Pengaruh Promosi, Gaya Hidup, Persepsi Resiko, dan Electronic Word of Mouth Terhadap Minat Beli Motor Listrik di Purwokerto - Evan Alesandro Wibowo,; Tri Septin Muji,; Dian Widyaningtyas,; Purnadi, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Electric motorcycle are innovative vehicles whose charging does not depend on petroleum, making them more environmentally friendly. The purpose of this study was to analyze the influence of promotion, lifestyle, risk perception, and electronic word of mouth on the interest in purchasing electric motorcycles in Purwokerto through a questionnaire with a purposive sampling technique. Based on the criteria, 100 respondents were obtained. This study used the SPSS test tool, with the research method used multiple regression analysis. The results showed that promotion and risk perception had a positive effect on the interest in purchasing electric motorcycle in Purwokerto. Meanwhile, risk perception and electronic word of mouth did not affect the interest in purchasing electric motorcycle in Purwokerto.